PERAN SOSIOLOGI HUKUM PADA PENEGAKAN HUKUM PELAKU UJARAN KEBENCIAN DI MEDIA SOSIAL: SEBUAH LITERATURE REVIEW - Vega Lidya Pratiwi (GoAcademica Research dan Publishing, 2023)
This literature review study is motivated by an empirical phenomenon that describes the existence of social media universally which is increasingly influential on human life in accessing news or information raised on social media. So that it can be ensured the creation of freedom of opinion in conveying aspirations which certainly shapes various public perceptions. In addition to the positive side received, it is undeniable that the negative side of social media must also exist, such as hate speech that is intended to insult, demean, make victims feel sick. This problem certainly cannot be ignored because it can affect a person's mental problems. The implications of these actions certainly have an impact on the emergence of physical injuries, mental, social, spiritual disorders and often even cause death. This literature is shown to theoretically analyze the role of legal sociology in law enforcement of perpetrators of hate speech on social media. The literature review method was carried out on five articles obtained from several internet databases. Keywords for article search are